What's the Cost? Measuring the Economic Impact of Pediatric Sepsis - Carlton, Erin F.; Weiss, Scott L.; Prescott, Hallie C.; Prosser, Lisa A. (Frontiers in Pediatrics, 2021)
Sepsis, life-threatening organ dysfunction secondary to infection, hospitalizes nearly 80,000 children each year in the United States. Most children survive sepsis. However, there is increasing recognition of the longer-term consequences of pediatric sepsis hospitalization on both the child and their family, including medical, psychosocial, and financial impacts. Here, we describe family spillover effects (the impact of illness on caregivers) of pediatric sepsis, why measurement of family spillover effects is important, and the ways in which family spillover effects can be measured.